Assessing the Economic, Demographic, and Agricultural Determinants of Wheat Production in Libya: Evidence from an ARDL Approach (2000–2023) - Jamal Ali Mohamed Ehdadan (Journal of Scientific and Human Dimensions, 2026)
Ensuring adequate wheat production remains a major challenge for Libya, where domestic supply continues to meet fall short of national demand. This study examines the key economic, demographic, and agricultural determinants of wheat production During 2000–2023.An Autoregressive Distributed Lag (ARDL) approach is utilized to investigate the short-run adjustments and long-run equilibrium relationships between wheat production and its key determinants., including barley production, crop prices, imports, population growth, and domestic demand. The results confirm the existence of a stable long-run relationship. Domestic demand plays a significant positive role, while wheat imports and population growth exert negative pressures on local output of wheat. The interaction between wheat and barley suggests that production decisions are influenced by broader agricultural conditions rather than simple crop substitution. These findings reflect structural constraints within the Libyan agricultural sector, particularly limited resources and Rising consumption pressures Strengthening domestic production therefore requires policies that improve productivity, Improved resource use, and control excessive of imports. This study provides an integrated econometric assessment of wheat production dynamics in a resource-constrained economy, offering insights relevant for food security policy in Libya.
Keywords: Wheat production; Food security; ARDL approach; Wheat imports; Libya